Monitoring the Impact of sanctions on the Russian Economy. Quarterly Report Vol. 2 - Vasily Astrov; Lisa Scheckenhofer; Camille Semelet; Feodora Teti (CESifo GmbH, 2024)
In 2023, Russia experienced a 3.5% economic growth, but forecasts for 2024 indicate a slowdown to 1.5% due to tightened monetary policies and the expected global economic slowdown. Despite large military spending and Western energy sanctions eroding budget revenues, fiscal deficits have been generally kept under control. Intensified scrutiny of third-country firms violating energy sanctions widened discounts on Russian oil prices in late 2023. Generally, Russian import patterns remained relatively stable. In particular, EU exports of economically critical and common high priority goods to Russia in November 2023 represent just 2% of its pre-war levels, underscoring the effectiveness of sanctions in halting direct exports. Besides China and Hong Kong, Türkiye and CIS countries became vital suppliers, meeting Russia's demand for economically critical goods and high-priority items.
Keywords: 330; Sanktion; Wirkungsanalyse; Russland